2012
DOI: 10.1177/1359105312462434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guided Written Disclosure Protocol on mood states and psychological symptoms among parents of off-therapy acute lymphoblastic leukemia children

Abstract: This study assesses the effects of Guided Written Disclosure Protocol on psychological distress in mothers and fathers of off-therapy acute lymphoblastic leukemia children. An experimental group participated in the writing intervention with a control group subject only to test-taking standards. The Symptom Questionnaire and Profile of Mood States were administered at baseline, post-intervention, and follow-up. Guided Written Disclosure Protocol had significant effects on the progressive reduction of anxiety, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Previous studies of WED in caregivers have reported reductions in anxiety (Martino, Freda, & Camera, 2013) and traumatic symptoms (Barry & Singer, 2001), in addition to improvements in general psychological health (Barry & Singer, 2001). Furthermore, only one study has focussed explicitly on caregivers of people with psychosis (Barton & Jackson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of WED in caregivers have reported reductions in anxiety (Martino, Freda, & Camera, 2013) and traumatic symptoms (Barry & Singer, 2001), in addition to improvements in general psychological health (Barry & Singer, 2001). Furthermore, only one study has focussed explicitly on caregivers of people with psychosis (Barton & Jackson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We reported in a previous article (Martino, Freda, & Camera, 2013) that writing affects health outcomes; in this article, we use a qualitative approach to explore the meaning-making processes underlying the writings of parents of children with acute lymphoblastic leukemia (ALL) in the off-therapy phase. Specifically, what are the processes of meaning making through which writing has worked?…”
Section: Narrative and Meaning-making Processes: Our Perspectivementioning
confidence: 99%
“…We chose the SQ (Fava & Kellner, 1982;Fava et al, 1983) as a sensitive and reliable tool for measuring the change of symptomatological aspects after a psychological intervention. We focused on anxiety because it is one of the main symptomatological aspects that emerged among the parents during the off-therapy phase (see Martino, Freda, & Camera, 2013). Moreover, the GWDP is effective at reducing anxiety, stress, and post-traumatic stress disorder (PTSD; Duncan et al, 2007;Gidron et al, 2002).…”
Section: Participants and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our view, it can be considered as a narrative (Margherita 2009) co-constructed within a group, like a device characterized by its therapeutic potentialities performing above all a transformative function (Bion 1961). The narrative is such that the story told contains, constructs links and hypothesis between experiences by connecting the present, past, future in framework involving sense and meaning (Angus & McLeod 2004;Freda 2011;Martino et al 2012). The narrative brings together emotional aspects, feelings and images that speak on various levels about the group, their relationships, and the context.…”
Section: The Fairy Tale In Group: the Functionsmentioning
confidence: 99%